Hubungan Kedisiplinan Guru dengan Motivasi Belajar Siswa Kelas Tinggi SD Negeri 21 Seppang Kecamatan Ujungloe Kabupaten Bulukumba - Sitti Jauhar; Sindhi Awalia; Asriadi Asriadi (Universtas Negeri Makassar, 2022)
This study is a quantitative study with a correlation design that aims to determine whether or not there is a relationship between teacher discipline and student motivation for high grade students at SD Negeri 21 Seppang. Based on the results of descriptive statistical analysis, the results of teacher discipline research have an average of 79,26 and a percentage of 79,26% with a good category and the learning motivation of high-class students has an average of 79.0625 and a percentage of 79.0625% with a good category. Based on the results of inferential statistical analysis, the tcount value (4,33391) is greater (>) the ttable value (1.66462) at the 5% significance level. Thus H0 is rejected and H1 is accepted. The results obtained in this study are that there is a significant relationship between teacher discipline and high grade students' learning motivation at SD Negeri 21 Seppang, Ujungloe District, Bulukumba Regency.